Late Quaternary megafaunal extinctions on the continents: a short review. (20th December 2014) - Stuart, Anthony John; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> This paper provides an overview of the contentious issue of global megafaunal extinctions in the Late Quaternary. The main proposed causes are 'overkill', environmental change or a combination of both. There are major objections to the other suggested causes. Extinctions were highly variable in their severity between different zoogeographical regions, with the greatest impact in North America, South America and Australia, but also substantial in northern Eurasia. Sub‐Saharan Africa and Southern Asia were much less affected. For northern Eurasia, detailed chronologies show a staggered extinction pattern, in which each megafaunal species exhibits unique and complex distributional shifts, culminating in extinction for some species and survival in others. Environmental drivers were clearly very important, although the possible role of humans is not yet clear. Alaska/Yukon also has a good radiocarbon record which also suggests a staggered extinction pattern. However, the available data for the rest of North America are largely unsatisfactory. South America also boasted spectacular extinct megafauna, but again the currently available dates are insufficient to reliably discern patterns or possible causes. Australia and New Guinea also suffered major losses, but extinctions probably occurred much earlier than elsewhere, so that establishing a chronology is especially difficult. Africa and Southern Asia have the least available data. In order to make meaningful progress, it is vital to establish a large database of reliable radiocarbon dates for each region made directly on securely identified megafaunal remains. The need is for much more high quality data, not more debate based on imperfect evidence. Copyright © 2014 John Wiley & Sons, Ltd.